TAFSIR KEBANGSAAN BERTAJUK TOLERANSI DI MEDIA SOSIAL: ANALISIS WACANA KRITIS VAN DIJK PADA TAFSIRALQURAN.ID - Muttaqin, Zaenal; Khiyaroh, Arifatul (Academic Journal of Islamic Principles and Philosophy, 2023)
This article discusses one of the websites that focuses on the study of the Qur’an and interpretation courses, namely the tafsiralquran.id website. This study specifically discusses the presentation model of national interpretation content with the theme of tolerance on the tafsiralquran.id website and the ideology carried by the website in building discourse and interpretation of the Koran. This research found that even though it is considered as an interpretation of social media, which is limited by regulations regarding writing on the internet, the website tafsiralquran.id still adheres to the guidelines of ’ulūmūl qūr’an in interpreting verses. The ideology promoted by the website is the ideology of moderate and nationalist interpretation. While the production of interpretation content on this website follows the problems that occur in society, including national issues that occur in Indonesia. This ideology is in line with the government’s vision and mission in realizing religious moderation.